Placing Information Skills in Context: As a Tool in Developing Teachers’ Writing Competency and Promoting Deeper Learning - Abdul Karim, Faziah (Journal of Social Transformation and Regional Development, 2021)
In recent years, library media experts have endeavored to move from teaching isolated library skills to teaching integrated information skills. Information skills are integrated effectively when the skills directly relate to the content area curriculum and classroom assignments and are incorporated in a logical and systematic information process model. This study examines the level of teachers’ ability to apply information skills in the Reports Writing of teachers attending the English Language Professional Development (CPD) Course. Although random sampling would ensure validity and reliability, there is no true sampling as the course participants are the only subjects here. The whole group of 24-course participants is involved in this study and is used as a sample of the study. A Likert scale set with a four-point Likert scale is used in assessing this study. The reliability value of questionnaire items in the pilot study was Cronbach alpha = 0.90. The results of this study were analyzed using Statistical Packages for Social Science (SPSS) version 22.0 using simple percentages and to obtain mean analysis, standard deviation, and correlation. (Mean = 3.12, SD = .52) locating information source, (Mean = 3.1, SD = .496) extracting relevant information, (Mean = 3.04, SD = .53) synthesizing the information and evaluating to communicate the information (Mean = 3.07, SD = .52). The findings also show the correlation of locating information sources with extracting relevant information (r = .975), synthesizing the information (r = .976), and evaluating to communicate the information (r = .984) is at a high level. To ensure that the principles of triangulation eliminate personal assumptions entering the findings, various instruments were also used. A pre-test and a post-test were given to assess respondents’ entry knowledge before the start of the course and their overall performance at the end of the course. The best result in the pre-test was in the ‘summary’ and the best score for the post-test was in ’Direct Quotations’. Assessing the respondents’ report writing was done to ascertain the effective and accurate application of information skills in their report writings. More than fifty percent of the course participants obtained a high score for their report writing marks. They had manifested a good mastery of information skills and in terms of precision of ideas and thoughts as well as coherence and cohesion in writing, the course participants have developed their competency highly and the process of deeper learning, in a recursive, mutually reinforcing cycle. The results of this study would be of considerable significance to lecturers or trainers in the teaching of report writing and preparing course participants to write with higher competency.